The interplay between attention deficit/hyperactivity disorder and internet addiction: executive dysfunction and insomnia as mediators and the role of physical activity - Liu, Fangtai; Zhong, Liping; Chen, Haiyu; Teng, Ziwei; Su, Yuhan; Chen, Jinliang; Qin, Yue; Luo, Qiong (Frontiers in Psychiatry, 2026)
BackgroundAttention Deficit/Hyperactivity Disorder (ADHD) and internet addiction (IA) are common among college students and often co-exist. This study investigated the relationship between ADHD symptoms, executive dysfunction, insomnia, and IA in Chinese college students.MethodsA cross-sectional study was conducted in June 2024 at six universities in Hunan Province, China. Demographic data and symptoms of ADHD, IA, executive dysfunction, insomnia, and physical activity were collected via interviews and self-reported questionnaires. Physical activity level was further quantified and categorized using metabolic equivalents (METs) method. Mediation models were performed to explore the path from ADHD to IA and the role of physical activity in IA symptoms.ResultsAmong 1925 students, 12.52% had ADHD symptoms, and 14.03% had IA symptoms. ADHD symptoms were related to IA symptoms (total effects: 0.38, p < 0.001; direct effect: 0.111, p = 0.003), mediated by insomnia (0.161, p < 0.001) and executive dysfunction (0.108, p < 0.001). Compared with no physical activity, moderate-level and high-level physical activities were negatively correlated with IA symptoms, with total relative standardized effects of -0.18 (p = 0.001) and -0.42 (p<0.001), respectively. The relative direct effect of high physical activity levels on IA symptoms was -0.29 (p<0.001), regardless of mediation by insomnia (-0.056 (95%CI, -0.094 to -0.021)) and executive dysfunction (-0.067 (95%CI, -0.105 to -0.033)).ConclusionADHD and IA symptoms are prevalent among Chinese college students. Executive dysfunction and insomnia mediate the relationship between ADHD and IA symptoms. Moderate and high-level physical activities were associated with reduced risk of IA symptoms, mediated by executive dysfunction and insomnia. Physical activity may help mitigate IA symptoms in college students.